2022
DOI: 10.3390/brainsci12030304
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Light EEG-Based Measure for Real-Time Stress Monitoring during Realistic Driving

Abstract: Driver’s stress affects decision-making and the probability of risk occurrence, and it is therefore a key factor in road safety. This suggests the need for continuous stress monitoring. This work aims at validating a stress neurophysiological measure—a Neurometric—for out-of-the-lab use obtained from lightweight EEG relying on two wet sensors, in real-time, and without calibration. The Neurometric was tested during a multitasking experiment and validated with a realistic driving simulator. Twenty subjects part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…The device has been validated and is capable of recording the EEG signal extremely accurately [ 26 ]. The sampling frequency was 250 (Hz).…”
Section: Methodsmentioning
confidence: 99%
“…The device has been validated and is capable of recording the EEG signal extremely accurately [ 26 ]. The sampling frequency was 250 (Hz).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding stress measurement, the literature proved that there is a correlation between cortisol and brain activity in beta (Seo and Lee, 2010 ). A stress neurometric based on parietal brain activity in the high beta band was effectively tested during laboratory multitasking and was validated during realistic driving, proving that it is possible to have reliable stress measurements using the following (Sciaraffa et al, 2022 ):…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the ability to classify mental workload associated with various laboratory tasks (e.g. N-back [13], mental arithmetic [14], Sternberg memory [15], auditory oddball target paradigm [16,17], visual search [17], and a laboratory version of air traffic control for vigilance tests [18]), as well as in more realistic task scenarios like flight [1,17,[19][20][21] or driving [1,22] simulation, using EEG signals. Typically in such studies, different levels of mental workload are induced by altering the difficulty of the task being performed or by introducing secondary tasks.…”
Section: Introductionmentioning
confidence: 99%